2010
DOI: 10.1186/cc9390
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory support withdrawal in intensive care units: families, physicians and nurses views on two hypothetical clinical scenarios

Abstract: IntroductionEvidence suggests that dying patients' physical and emotional suffering is inadequately treated in intensive care units. Although there are recommendations regarding decisions to forgo life-sustaining therapy, deciding on withdrawal of life support is difficult, and it is also difficult to decide who should participate in this decision.MethodsWe distributed a self-administered questionnaire in 13 adult intensive care units (ICUs) assessing the attitudes of physicians and nurses regarding end-of-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 40 publications
1
38
0
3
Order By: Relevance
“…Recent research conducted in a number of Brazilian hospitals has shown that in cases where patients are unable to take part in end-of-life care discussions due to their clinical condition, most physicians are less likely to disagree with nurses and family members. (24) This conclusion agrees with that of another study that was conducted in the US. (25) Several studies have stressed the relevance of medical team and patient/family member communication.…”
Section: Discussionsupporting
confidence: 91%
“…Recent research conducted in a number of Brazilian hospitals has shown that in cases where patients are unable to take part in end-of-life care discussions due to their clinical condition, most physicians are less likely to disagree with nurses and family members. (24) This conclusion agrees with that of another study that was conducted in the US. (25) Several studies have stressed the relevance of medical team and patient/family member communication.…”
Section: Discussionsupporting
confidence: 91%
“…During the course of a patient's stay in the ICU, family members must often assume responsibility over health‐related decision making, including choices about diagnostics, treatment and therapeutic care. Family member involvement in decision making was the subject of 7 quantitative and 10 qualitative studies . Amongst the qualitative studies, five use in‐depth interviews to explore how surrogate‐decision‐makers participate in decision making around life support .…”
Section: Resultsmentioning
confidence: 99%
“…Another significant finding from our study is that what physicians said they would do differed in 44% of cases from what they believed was best for the patient. Despite these concerns, withdrawal and withholding of LST are increasingly reported EOL practices in Brazil [3], and in some circumstances, even desired by families [38]. Legal concerns, followed by team and societal opinion, were the most common obstacles to following the course of action believed to be best.…”
Section: Discussionmentioning
confidence: 99%